2017
DOI: 10.1016/j.ijhcs.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Interface Design (AID) for enhanced computer accessibility and rehabilitation

Abstract: This study was aimed at the development of a nonintrusive, biosensor based, Adaptive Interface Design (AID) that utilizes its users' physical abilities (rather than focusing on their disabilities), while simultaneously honoring their integrity and needs. The target users for this study were patients with arthritis in the hand. The AID comprises of eye tracking and data glove technologies, the latter of which will be used to measure the user's physical ability as it translates hand gestures into computer contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 55 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Other oddities include: (i) mis-citing another questionnaire with the same acronym "Game Engagement Questionnaire" [4,5]; (ii) citing the KidsGEQ [44], a poster containing only seven example items, for a study with university students; (iii) citing the Future Play [41] and Fun & Games [10] which do not include any GEQ items; (iv) citing the Social Presence in Gaming Questionnaire (SPGQ) of which items are different from the core GEQ [43,60]; (v) citing the URL of the homepage of the research lab of which the GEQ originators were members, but without specifying the location of the document [63]; (vi) providing the authors and title of the GEQ without publication year or status [21]. These add up to 8 instances (or more than 10%) of the reviewed papers.…”
Section: Confusing and Untraceable Referencesmentioning
confidence: 99%
“…Other oddities include: (i) mis-citing another questionnaire with the same acronym "Game Engagement Questionnaire" [4,5]; (ii) citing the KidsGEQ [44], a poster containing only seven example items, for a study with university students; (iii) citing the Future Play [41] and Fun & Games [10] which do not include any GEQ items; (iv) citing the Social Presence in Gaming Questionnaire (SPGQ) of which items are different from the core GEQ [43,60]; (v) citing the URL of the homepage of the research lab of which the GEQ originators were members, but without specifying the location of the document [63]; (vi) providing the authors and title of the GEQ without publication year or status [21]. These add up to 8 instances (or more than 10%) of the reviewed papers.…”
Section: Confusing and Untraceable Referencesmentioning
confidence: 99%
“…Another approach in the AUI evaluation has been put forward by Paramythis et al [43] that provide a method to separately evaluate each adaptive system constituents through the decomposition of adaptation "from the perspective of HCI-oriented evaluation": adaptation is no longer considered as a singular process. Other approaches concern the adaptive interface evaluation in terms of cost and benefit [44] user's error [45], cognitive workload predictability and accuracy [46], and accessibility [47].…”
Section: Research Backgroundmentioning
confidence: 99%
“…Recently, several studies [ 11 – 13 ] were conducted on PwPD to assess motor dysfunction using commercially available non-contact video and RGB-D based sensors. Result showed that the video-based system could detect bradykinesia and dyskinesia in the clinical environment.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also focused on another commercially available device, the Leap Motion controller (LMC), which incorporates a 3D camera that is connected to a computer and is claimed to measure positional data accurate to within 0.01 mm [ 14 ]. LMC was primarily employed with video games, such as in the study of Lin [ 13 ], where it was used to track the hand movements to enhance the computer accessibility in rehabilitation. Similarly, in the study of Blazica [ 15 ], LMC was used with kinetic sensor to achieved the full kinematics of movement during game play.…”
Section: Introductionmentioning
confidence: 99%